INOVASI TEKNOLOGI DALAM MENINGKATKAN KEDISIPLINAN SANTRI MELALUI PLATFORM SEKOLAH PINTAR MOBILE : STUDI KASUS DI PONDOK PESANTREN MATHOLI'UL HIKMAH. - Salamatul Fauziyah, Fadhilatus; Ahmad Saiful Rizal; Achmad Abdul Azis (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study aims to analyze the implementation of technological innovation through the Smart School Mobile Platform (PSP) in improving students’ discipline at Pondok Pesantren Matholi’ul Hikmah, as well as to identify its impacts and challenges. This research employs a qualitative method with a case study approach. Data were collected through participatory observation, in-depth interviews with caregivers, teachers, students, and parents, as well as documentation of the digital attendance system. Data analysis used the Miles and Huberman model with source and method triangulation to ensure data validity. The findings reveal that the implementation of PSP Mobile significantly enhances students’ discipline, particularly in punctuality, responsibility, and regularity in learning and worship activities. The platform also strengthens caregivers’ supervision and parents’ engagement through real-time monitoring, while improving the efficiency and transparency of pesantren management. Challenges include limited digital literacy among parents, internet dependency, and high initial operational costs. Overall, PSP Mobile effectively supports adaptive and participatory pesantren governance in the digital era without neglecting the traditional Islamic educational values that characterize pesantren education.